Capítulo 8 - Aprovechamiento de subproductos frutihortícolas como alternativa para la prevención de PDA - Polenta, Gustavo Alberto (2023)
As part of the activities that prevent food loss and waste (FWD) and depending on its productive profile, the recovery of high value-added compounds is strategic for our region in general, and for Argentina in particular. This topic, which is arousing growing interest at the academic and business level, can promote the viability and diversification of regional economies, both rural and urban, creating new quality jobs in innovative industries, and mitigating the environmental impact of industrial activities through through optimization in the use of primary resources. However, due to its complexity, a multidisciplinary approach and the involvement of different sectors are necessary. In this sense, an example to imitate in our region would be the so-called Food Waste Recovery Network (Food Waste Recovery Group), which constitutes an open innovation network started in the European Union and which currently has a large number of researchers. and professionals partners from more than 60 countries, forming a platform for the exchange of knowledge and the implementation of joint projects. In a first FLW estimation exercise carried out in Argentina, in which work was done on the main agri-food sectors representative of the country's economic activity, in terms of production, exports and relative importance for the economies regional, a total estimated volume of FLW was established of 16 million tons (T) of food in its “primary equivalent”. This value represents 12.5% ​​of agri-food production, where “losses” explain 90% of the total, while “waste” only 10%. Although these figures are well below of the world average (30% of total FLW), are also alarming, since they mean 14.5 million T of “loss” and 1.5 million of T for “waste”. Among the different sectors evaluated, both in the horticultural sector as in the fruit sector, the percentages rise to 45 % and 55%, similar to the world average (45%) and which coincide with other observations that indicate that in Argentina only the half of the fruits and vegetables that are harvested, and approximately 80% of this loss is recorded in the production and post-harvest stages. and processing. Based on these data, the need to reinforce clearly emerges investment in research and development on this topic, so as to allow the food industry to innovate in technologies that guarantee safety, extend the useful life of products, minimize waste, Extend product development with minimal processing and increase the efficiency of the chain through the recovery of compounds of interest from effluents and processing waste.